2017
DOI: 10.1063/1.4977257
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-electrical properties and resistance stability of silver coated yarns

Abstract: Abstract. Thermal-electrical properties and resistance stability of silver yarns was researched to evaluate the performance be a heating element. Three samples of silver coated yarns with different linear density and electrical resistivity, which obtained by market. Silver coated yarns were placed at the high temperature condition for ageing. The electrical resistances of yarns were increased with the ageing process. The infrared photography instrument was used to measurement the temperature variation of silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Another research work was carried out to test the electro-thermal stability of silver yarn or silver-coated yarn by performing an oven aging test; the results found better electrical resistivity of silver yarn by showing a strong linear density. At a voltage of 9 V, that resistivity made the samples capable of obtaining higher temperatures [ 77 , 78 ]. Kexia et al [ 78 ] showed the relation of temperature and the resistance of wool and silver yarn made conductive electro-thermal knitted fabric ( Figure 4 B).…”
Section: Advanced Heating Textiles and Their Performancesmentioning
confidence: 99%
“…Another research work was carried out to test the electro-thermal stability of silver yarn or silver-coated yarn by performing an oven aging test; the results found better electrical resistivity of silver yarn by showing a strong linear density. At a voltage of 9 V, that resistivity made the samples capable of obtaining higher temperatures [ 77 , 78 ]. Kexia et al [ 78 ] showed the relation of temperature and the resistance of wool and silver yarn made conductive electro-thermal knitted fabric ( Figure 4 B).…”
Section: Advanced Heating Textiles and Their Performancesmentioning
confidence: 99%
“…So the analytical equation could accurately model the electro-thermal characteristics of the thermal fabrics under an applied electric current and compute the temperature at a certain time. Li et al [20] evaluated the thermal-electrical stability of heating element with silver yarn. The results showed a larger linear density made the silver coated yarns better electrical resistance stability in the oven ageing experiment.…”
Section: Flexible Heating Fabricmentioning
confidence: 99%
“…An infrared photographic instrument is used to measure the temperature variation on the electrically conductive yarns through which an electric current of different power flows. High temperatures increase the electrical resistance of the yarn [ 12 , 13 ]. Thermal cameras are also used, which take thermal photos through a textile circuit in which the electrically conductive yarns are under different voltage values [ 14 ].…”
Section: Introductionmentioning
confidence: 99%